-6x-3.9=-1x-4.1

Simple and best practice solution for -6x-3.9=-1x-4.1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-3.9=-1x-4.1 equation:


Simplifying
-6x + -3.9 = -1x + -4.1

Reorder the terms:
-3.9 + -6x = -1x + -4.1

Reorder the terms:
-3.9 + -6x = -4.1 + -1x

Solving
-3.9 + -6x = -4.1 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-3.9 + -6x + x = -4.1 + -1x + x

Combine like terms: -6x + x = -5x
-3.9 + -5x = -4.1 + -1x + x

Combine like terms: -1x + x = 0
-3.9 + -5x = -4.1 + 0
-3.9 + -5x = -4.1

Add '3.9' to each side of the equation.
-3.9 + 3.9 + -5x = -4.1 + 3.9

Combine like terms: -3.9 + 3.9 = 0.0
0.0 + -5x = -4.1 + 3.9
-5x = -4.1 + 3.9

Combine like terms: -4.1 + 3.9 = -0.2
-5x = -0.2

Divide each side by '-5'.
x = 0.04

Simplifying
x = 0.04

See similar equations:

| -8+3b=2b-4 | | -6x-3.9n=-1x-4.1 | | 0.7+y=-1.24 | | U=5(4n+33)+9(n+1) | | 1/2÷22 | | -7b^2-34b-24=0 | | 4x-3=3y+9 | | 1x-2y=168 | | 3m+10+2=180 | | 79600*50+15800(100)+3800(150)= | | 4(-1+3x)+3=-3x-1 | | =-24+2(y-9) | | 5x-5+31x+5=180 | | -85=6a-(1-8a) | | 11+1x=13-1x | | 9/14x7/6 | | 3q+3=180 | | 3q+3=18 | | 5(X+5)=100 | | 2/5x-6=9 | | X(14x)=350 | | 11x=209-13y | | 24xn=-8 | | (5.5+2x)x=5.1 | | x-12+4=16 | | .5x^2=2x+0.5 | | 79600*50+15800*(50+x)+3800*(50+2x)=6.13 | | 6(x+33)=222 | | 65x=55(x+15) | | 1+8x-8x=-10 | | X/9-8=7 | | C=1+9 |

Equations solver categories